Tutorial chat: a case study of synchronous communication in a learning environment - Malcolm Rutter (Association for Learning Technology, 2006)
This case study describes the use of a web-based synchronous chat application, run during computing tutorials. The chat room was moderated by a paid demonstrator, who assisted and encouraged students whenever possible. Most of the discussion was banter, which acted as a lubricant for relevant factual communication. Students were permitted a degree of anonymity, but nevertheless learned to treat the facility in a useful manner. The application and its mode of employment were found to be both motivating and supportive. Use was evaluated by questionnaire and an analysis of student input. As a result of the experience, it is suggested that abuse will certainly occur and may be minimised by technical improvements, but never eliminated. The Rogerian approach adopted was found to have transferred emphasis from teaching a topic to the learning of generic skills.